Optimalisasi Bumdesma kampung batik based on One Village One Product: One Village One Prpduct - Mabruroh (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2025)
Madura Island has great potential in developing the creative economy, especially because of its rich arts. Pamekasan Regency, as one of the regions in Madura, has artistic potential that can be transformed into a creative industry. However, the problem of capital is the main obstacle. Therefore, the utilization of Village-Owned Enterprises (BUMDes) is a solution to optimize potential and overcome these problems. To overcome this problem, optimization and transformation of BUMDes is needed through the One Village One Product (OVOP) concept. In addition, to create a capital concept that is in accordance with the principles of sharia economics and halal lifestyle, all BUMDes activities must be based on the Sharia Contract. This study uses a descriptive qualitative method to analyze factual problems in the related village. The results of this study are a broader concept of optimizing BUMDes performance, not only focusing on one village one commodity, but also collaborating with several villages with similar potential to produce one superior commodity. In this case, BUMDESMA Kampung Batik was formed. In its formulation, verse analysis is used and as a reinforcement of the Sharia Contract, using Ibn Kathir's interpretation as a reference to regulate capital in accordance with sharia principles. This optimization effort will be carried out from upstream to downstream by forming a community of raw material producers, a community of motif and coloring, a community of designers and convection, and a community of batik waste management.